New Zealand Households and the 2008/09 Recession - Christopher Ball; Michael Ryan (New Zealand Government, The Treasury, 2013)
This paper seeks to quantify how the welfare of different types of household changed between 2006/07 and 2009/10; a period which included the 2008/09 recession. We use three measures of household welfare: income, expenditure and the equivalent variation metric. The equivalent variation is a measure of the welfare lost owing to price changes. Using household level data from the Household Economic Survey (HES), we allocate households into "types" on one dimension (for example age group) as is traditional in the literature but also cluster the data into 12 different representative households based on 9 demographic and economic dimensions. Households in low income groups, with children and/or who rent were particularly impacted by the recession in terms of welfare losses owing to price changes. However we find that those in low income groups had strong increases in expenditure; furthermore the welfare gains from this increased expenditure more than offset the welfare losses from the price changes.
Keywords: D12; D6; C1; 330; Consumer; Welfare; Quantitative Methods; Privater Haushalt; Soziale Lage; Konjunktur; Statistische Methode; Neuseeland